Development of online directory of Islamic higher education in Java Island - Roudhotul Jannah; Djoko Andrijono (Jurnal Penelitian, 2022)
Currently, we have entered the industrial era 4.0 where technology and information are developing very quickly so that a lot of data can be obtained easily by the public, but the credibility of this information cannot be accounted for because the source of information is unclear. It is known, with these problems and supported by sophisticated technology, a new search medium has emerged which is called an online directory. The contents of online directories include important information such as names of organizations, institutions, or individuals, addresses, telephone numbers, as well as credible sources. Many people, especially high school graduates, and the equivalent want to continue their education in tertiary institutions, one of which is an Islamic university. Thus the online directory of Islamic universities in Java made by this author can be used as a reference for people who wish to continue their education at Islamic universities in Java but users also need to find further information through the website link that is already listed in the directory because the information is in the directory is not 100% complete.